THE LOGISTICS SUPPORT AND SECURITY ISSUES IN THE BORDER REGION - Altangerel Dalantai (International Journal of Innovative Technologies in Social Science, 2026)
This study explores the significance of cross-border logistics in international trade, focusing on the management and coordination of goods transportation across national borders. The process involves key activities such as transportation, customs clearance, and documentation to ensure efficient and timely product delivery while adhering to regulations and minimizing costs. Each country has its own regulations, tariffs, and customs requirements that businesses must navigate to avoid delays and penalties. The complexity of supply chains involves multiple stakeholders, including carriers, customs agents, and brokers, whose coordination may be hindered by operational hour differences and communication barriers. Therefore, the study examines how partnering with specialized logistics providers can improve operational efficiency by leveraging their customs process expertise. The unique geographical and ecological characteristics of the Gobi Desert add further complexities, including environmental concerns and impacts on local herding communities. Strategic solutions highlighted in the study include partnering with specialized logistics providers, implementing advanced tracking technologies, establishing integrated logistics centers, and developing comprehensive mobilization strategies. Effective logistics management at border operations is essential for enhancing Mongolia’s trade competitiveness and economic performance while considering environmental protection and community welfare. The research contributes to understanding how landlocked nations can optimize cross-border logistics operations in challenging geographical environments.